Anxiety, depression, and birth outcomes in a cohort of unmedicated women. (19th May 2021) - Ossola, Paolo; Ampollini, Paolo; Gerra, Maria Lidia; Tonna, Matteo; Viviani, Daniela; Marchesi, Carlo
Abstract: Background: Even though most of the systematic reviews suggest that depression and anxiety are related to poor neonatal outcomes, it is not yet clear whether a dose–response effect exists. Aim: The aim of the present study is to evaluate the amount of depressive and anxiety symptoms in a cohort of pregnant women and its effect on their newborns. Methods: Two hundred ninety-nine women were assessed for anxiety and depressive disorders and anxious and depressive symptoms at near monthly intervals throughout pregnancy. At the time of delivery, we collected the newborns' gestational age, birth weight and the Apgar score at 1 and 5 min. Results: Sixty-seven women were diagnosed as depressed and 43 had an anxious disorder. After controlling for confounding variables only the overall levels of anxiety during pregnancy were negatively associated with birth weight ( B = −5.76; 95% CI = −10.96, −2.81), suggesting the existence of a "dose–response" effect. The birth outcomes in mildly depressed pregnant women were similar to those of nondepressed women. Conclusion: Anxiety symptoms, beyond a categorical diagnosis, are associated with low birth weight and should be recognized and properly treated during pregnancy.